Quality of Life and Associated Factors in Patients Suffering From Burns - Zakiyeh Jafaryparvar; Masoomeh Adib; Atefeh Ghanbari Khanghah; Ehsan Kazem Nezhad Leyli (Guilan University of Medical Sciences, 2018)
Introduction: The advances in the field of burn treatment resulted in increased survival of burn patients, which led to increased attention to the issues associated with the quality of life. The assessment of the quality of life and the associated factors might help in identifying the needs of affected patients and designing suitable therapeutic and supportive programs. Objective: The present study aimed to determine the quality of life and the associated factors in patients suffering from burns hospitalized at the subspecialty burn and plastic surgery center in Rasht city. Materials and Methods: The present cross-sectional analytical study consisted of 60 burns patients collected through systematic random sampling. The instrument used included Burn-Specific Health Scale-Brief (BSHS-B) along with a questionnaire for recording the demographic information as well as the complications and problems after the burn (itching, hypertrophic scar, colloid, hypopigmentation, and hyperpigmentation). The data were analyzed by descriptive statistics (frequency estimation, mean, and standard deviation) and inferential statistical tests (Friedman and linear regression tests). Results: The mean post-burn quality-of-life total score was 76.9±20.74; the patients presented substantial problems regarding heat sensitivity of the burnt site (61.75%), and the extent of burns was a predictive factor of the quality of life [P=0.0001, 95% Confidence Interval (CI)=-1.65 to -0.6, B=-1.133]. Conclusion: Despite the advances achieved in treating patients with burns, the subsequent problems and complications are yet challenging. Also, the low-degree burns can be considered as a factor affecting the quality of life of these patients.